Modern and Interdisciplinary Problems in Network Science : A Translational Research Perspective - Chen, Zengqiang; Dehmer, Matthias; Emmert-Streib, Frank; Shi, Yongtang; Taylor and Francis (Boca Raton, FL : CRC Press, 2018)
Modern and Interdisciplinary Problems in Network Science: A Translational Research Perspective covers a broad range of concepts and methods, with a strong emphasis on interdisciplinarity. The topics range from analyzing mathematical properties of network-based methods to applying them to application areas. By covering this broad range of topics, the book aims to fill a gap in the contemporary literature in disciplines such as physics, applied mathematics and information sciences.
Table of Contents -- Chapter 1: The Spread of Strategies Predicted by Artificial Intelligence in Networks -- Chunyan Zhang, Nankai University, China -- Chapter 2: The Spread of Multiple Strategies in the Complex Networks -- Jenlei Zhang, Nankai University, China -- Chapter 3: The epidemic spreading processes in complex networks, Chengyi Xia, Tianjin University of Technology, China -- Chapter 4: Measurements for Investigating complex networks -- Z. Chen; Y. Shi; M. Dehmer; Nankai University, China, Austria -- Chapter 5: Overview of Social Media Content and Network Analysis -- Mohammed Ali Al-Garadi, University of Malaya, Kuala Lumpur, Malaysia -- Chapter 6: Analysis of Critical Infrastructure Network -- D. Rehak, P. Senovsky, M. Hromada; VSB Technical University of Ostrava, Czech Republic -- Chapter 7: Evolving Networks and their Vulnerabilities, -- Abbe Mowshowitz, Valia Mitsou, Graham Bent -- Chapter 8: Review of structures and dynamics of economic complex networks: Large scale payment network of Estonia -- Stephanie Rendn de la Torre, Tallinn University of Technology, Estonia -- Chapter 9: Predicting Macroeconomic Variables using Financial Networks Properties -- Petre Caraiani, Institute for Economic Forecasting, Romanian Academy, Romania -- Chapter 10: Anomaly Detection in Complex Networks -- Yaser Yasami, Department of Computer Engineering, Payame Noor University (PNU), Tehran, Iran -- Chapter 11: Finding Justice through Network Analysis -- Radboud Winkels, PPLE College Amsterdam, Holland
Includes bibliographical references and index.
Also available in print format.
Keywords: Complex networks; Dynamics using networks; Graphical models; Machine learning; Network analysis (Planning); Electronic books